PROBLEMATIKA PENERAPAN E-LEARNING DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN KOTA BATU PADA MASA PANDEMI - Agung Rahmat Hidayatullah; Anwar Sa’dullah; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
As the times progress, there are also more problems that must be faced in various field, including in the field of education. With te development of technology used in the learning process, an educator must also always develop so that the learning process runs as expected. The emergence of pandemic also hampered learning, both the obstacles experienced by educator,student, the learning system and in the process of its implementation. The existence of this pandemic has made many of the obstacles experienced even more serious, but with the problem there must be a solution that will solve the problem. With the development of this technology can be used as a solution in the field of education. In education the learning process is very important. One of the technologies used in solving problems in learning is e-learning. The emergence of elearning which can help in the learning process. By utilizing e-learning, teachers can maximize the learning process during a pandemic and at the same time take advantage of sophisticated technology for effective learning. With e-learning, educators are able to develop in improving education. Not only educators, student can also develop as expected. And learning will go well and efficiently as expected.